PENINGKATAN KETERAMPILAN MEMBACA DAN MENULIS AKSARA JAWA MELALUI PAPAN AKSARA JAWA (PASAR JAWA) PADA SISWA KELAS IV SD N NGOTO - Sari, Pristiana Russita; Nartani, C Indah (Universitas Sarjanawiyata Tamansiswa, 2020)
The Javanese script media board (Pasar Jawa) is an interactive Javanese script learning board where the board is used as a media for Javanese teacher training. The purpose of this study is to increase student activity, student interest, increased reading, and writing skills in the Javanese script. This research is a classroom action research (CAR) conducted at Ngoto Elementary School in Bantul Regency. The subjects in this study were fourth-grade students in semester 1 of 2019/2020, with a total of 28 students. Research made by the object of research is the ability to read and write Javanese script. The data analysis technique used in this research is a quantitative descriptive technique. Data collection techniques are using observation and tests. This research was carried out through the pre-cycle cycle, the first cycle, and the second cycle.